KARAKTER KERJA KERAS DAN KARAKTERISASINYA DALAM NOVEL PARA PENJAHAT DAN KESUNYIANNYA MASING-MASING - Azizi, Asmaul Farida; Anggraini, Purwati (Balai Bahasa Jawa Tengah, 2019)
ABSTRACTThis study aims to obtain the character and characterization of the main characters in the novels of the villains and their silence by Eko Triono. This research is a qualitative descriptive study. Data comes from the novels of the villains and their silence by Eko Triono. The data collection technique used is to read literary works in the form of novels of the villains and their silence and mark the descriptions that are in accordance with the context under study. The results and discussion about the character of hard work in accordance with the novel and its characterization. The study of the novels of the Criminals and the Silence of Each of these uses a Psychological Study that leads to the human nature. Results and discussion contain motivating, economic factors, and national development issues that require leaders to do hard work. The hard work character is shown by the author through characterization in the form of indirect characterization and direct characterization.?Keyword: Literary, Character, Characterization